1970
DOI: 10.1029/jb075i017p03399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of observational errors on the resolution of surface waves at intermediate distances

Abstract: In this paper a simple procedure is shown that permits the estimation of resolution for a given set of data having specified measurement errors. For estimation of the resolution obtainable with a given set of data, it is not sufficient to combine the partial derivatives of the observed quantities with respect to the parameters at depth; since the resolution is severely limited by the errors of measurement, these errors must also be considered. The determination of shear velocity for the crust and upper mantle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
3

Year Published

1972
1972
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 10 publications
0
37
0
3
Order By: Relevance
“…Inversion theory (BACKUS and GILBERT, 1967, 1968, 1970 in its stochastic form (DER et al, 1970;JORDAN and FRANKLIN, 1971) applied to the Rayleigh-wave attenuation data yields an average internal friction model of shear waves for this ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Inversion theory (BACKUS and GILBERT, 1967, 1968, 1970 in its stochastic form (DER et al, 1970;JORDAN and FRANKLIN, 1971) applied to the Rayleigh-wave attenuation data yields an average internal friction model of shear waves for this ocean.…”
Section: Introductionmentioning
confidence: 99%
“…was also found that Love-wave dispersion contributes less information about earth structure than Rayleigh-wave dispersion (Der et al, 1970;Braile and Keller, 1975). Since, in general, the maxima of the Rayleigh-wave partial-derivative curves are larger and narrower than those of the corresponding Love-wave curves, Rayleigh waves give better resolution than SLove waves.…”
Section: Itmentioning
confidence: 99%
“…(ii) It is well known that group and phase velocity observations provide basically the same information about the earth model (Der, et al, 1970;Wiggins, 1972). Pilant and Knopoff (1970) Preliminary inspection of data showed that the quality of Love-wave data was inferior to that of Rayleigh-wave data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dispersion measurements equalize the weighting and have been used to estimate earth structure for more than four decades (e.g. Haskell, 1954, Brune, 1969Der, et al, 1970;Braile and Keller, 1975). Observed dispersion can be used to constrain portions of the subsurface structure along the propagation path but substantial trade-off in the details of the lower crust and upper mantle are difficult to control without additional information.…”
Section: Fundamental-mode Surface-wave Dispersionmentioning
confidence: 99%